Risks for Preeclampsia and Small for Gestational Age: Predictive Values of Placental Growth Factor, Soluble fms-like Tyrosine Kinase-1, and Inhibin A in Singleton and Multiple-Gestation Pregnancies - Boucoiran, Isabelle; Thissier-Levy, Sarah; Wu, Yuquan; Wei, Shu-Qin; Luo, Zhong-Cheng; Delvin, Edgard; Fraser, William D.; Audibert, Francois; null (American Journal of Perinatology, 2013)
Objective To determine the accuracy of placental growth factor (PlGF), soluble fms-like tyrosine kinase-1 (sFlt-1), and inhibin A in singleton and multiple-gestation pregnancies for predicting preeclampsia (PE) and small for gestational age (SGA).Study Design A prospective cohort nested in a randomized controlled trial of antioxidant supplementation for the prevention of PE. Plasma biomarkers were evaluated at 12 to 18 (visit 1) and 24 to 26 (visit 2) weeks' gestation and expressed as adjusted multiples of the median.Results Multiple-gestation pregnancy (74/772) had a significant impact on all biomarkers' levels. PlGF was the best predictor of PE and SGA. At a 10% false-positive rate, PlGF at visit 1 had 21% sensitivity for predicting PE in singleton versus 60% in multiple-gestation pregnancies. PlGF at visit 1 had a 31% sensitivity in singleton and 27% in multiple-gestation pregnancies for SGA prediction.Conclusion PlGF level was a good predictor of subsequent PE as early as 12 to 18 weeks in multiple-gestation pregnancies but was not clinically useful enough to be used as a single marker.
Keywords: multiple gestation; PlGF; preeclampsia; sFlt-1; small for gestational age